1996
DOI: 10.1007/bf01877137
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and biological characteristics ofTyphula ishikariensis isolates from Norway

Abstract: Isolates of Typhula ishikariensis, a snow mold fungus, were collected from five localities in Norway. They were divided into three groups according to genetics, cultural morphology, etc. Group I grew normally at 10 ~ Its mating patterns with Japanese taxa were variable: compatible with both biotypes A and B; compatible with biotype A but incompatible with biotype B; and incompatible with both biotypes. Group I was prevalent in southern inland districts such as Buskerud, Oppland, and Hedmark. Group II had small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 10 publications
2
30
0
Order By: Relevance
“…Matsumoto et al (1982Matsumoto et al ( , 1983 found two intersterility groups (biotypes A and B) within Japanese isolates but included them in a single species, T. ishikariensis, because these biotypes could be genetically related through North American taxa. Matsumoto et al ( , 1996 also divided Norwegian isolates into three groups (groups I, II, and III) based on cultural characteristics and mating reactions with Japanese biotypes. Finally, Matsumoto (1997) classifi ed this fungus into two biological species (biological species I and II) based on morphologies and mating reactions.…”
Section: Basidiomycetesmentioning
confidence: 99%
“…Matsumoto et al (1982Matsumoto et al ( , 1983 found two intersterility groups (biotypes A and B) within Japanese isolates but included them in a single species, T. ishikariensis, because these biotypes could be genetically related through North American taxa. Matsumoto et al ( , 1996 also divided Norwegian isolates into three groups (groups I, II, and III) based on cultural characteristics and mating reactions with Japanese biotypes. Finally, Matsumoto (1997) classifi ed this fungus into two biological species (biological species I and II) based on morphologies and mating reactions.…”
Section: Basidiomycetesmentioning
confidence: 99%
“…In Norway, the basidiomycetous snow mould fungus, Typhula ishikariensis was divided into three groups (I, II and III) based on their mating reaction (Matsumoto & Tronsmo 1995, Matsumoto et al 1996. T. ishikariensis group III is prevalent in the northernmost part of Norway (Matsumoto & Tronsmo 1995, Matsumoto et al 1996, Greenland (Hoshino et al 2006), and Svalbard (Hoshino et al 2003).…”
Section: Effect Of Abiotic Factors On Thermal Dependencementioning
confidence: 99%
“…T. ishikariensis group III is prevalent in the northernmost part of Norway (Matsumoto & Tronsmo 1995, Matsumoto et al 1996, Greenland (Hoshino et al 2006), and Svalbard (Hoshino et al 2003). The distribution pattern of this fungus indicates that group III is more adapted to low temperatures than groups I and II.…”
Section: Effect Of Abiotic Factors On Thermal Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…Two psychrophilic snow moulds Spirorbis borealis and Typhula ishikariensis are also widely distributed not only in the cool temperate zone and frigid zone but also in Arctic regions such as Alaska and the Yukon (Lebeau and Longston 1958; McBeath 2002), Greenland (Hoshino et al 2006), Finnmark (northern Norway: Årsvoll 1975; Matsumoto and Tronsmo 1995; Matsumoto et al 1996), Iceland ( S. borealis not found: Kristinsson and Guðleifsson 1976; Hoshino et al 2004), Lapland (northern Finland and Sweden: Jamalainen 1949, 1957; Ekstrand 1955), Svalbard (Hoshino et al 2003), Russian Arctic (Tkachenko 2013). Their distribution pattern suggests that S. borealis and T. ishikariensis are highly adapted to the Arctic environment.…”
Section: Introductionmentioning
confidence: 99%